“I believe that my two tongues love each other cela ne m’étonnerait pas”: Self-Translation and the Construction of Sexual Identity - Guldin, Rainer (TTR)

(untitled) (Association canadienne de traductologie, 2007)
AbstractIn this paper I would like to explore the work of five bilingual writers focusing on the different narratives they develop in their use of (self-)translation as a textual strategy to fashion a sexual persona. Julia(e)n Green’s Le langage et son double/The Language and its Shadow and Louis Wolfson’s Le Schizo et les langues create narratives of severance and disjointing. The self-translational activity is used here to create perfectly separated spheres of (sexual) identity. Raymond Federman’s A Voice within a Voice and Christine Brooke-Rose’s Between, on the other hand, develop narratives of merging and mixing. The self-translating activity is viewed as a constant shifting and moving of sexual roles taking place in a sphere outside the conscious control of the writer. The final part of the paper will be dedicated to a discussion of Abdelkebir Khatibi’s Amour bilingue that fictionalizes the functioning of bilingualism and self-translation in terms of sexual roles, introducing, this way, a post-colonial dimension missing in the other texts.